The Effect of the PODE Learning Model Assisted by Digital Pop-Up Books on Science Conceptual Understanding and Critical Thinking Skills of Elementary Students - Muntaqiyah, Inayatul; Bektiarso, Singgih; Wardani, Rizki Putri (Jurnal Pendidikan MIPA, 2024)
One of the fundamental skills in science learning is concept understanding and critical thinking. However, science learning in schools has not focused on developing these two abilities. The purpose of this research is to examine the effect of the PODE learning model assisted by a digital pop-up book on the understanding of science concepts and critical thinking skills of elementary school students. The method applied in this study is experimental with a quasi-experimental design through a post-test-only non-equivalent control group approach. Based on the data analysis, it was found that PODE learning assisted by digital pop-up book media has a significant effect on concept understanding and critical thinking skills. Multivariate analysis showed a significant difference simultaneously on both dependent variables with a significance value of 0.000. Referring to the data obtained in this study, researchers suggest using the PODE model assisted by digital pop-up book media to improve students' understanding of science concepts and critical thinking skills. For future researchers, it is recommended to conduct longitudinal research on the PODE model and digital pop-up book media, as well as examine its effect on other variables such as creative thinking skills, higher-order thinking skills (HOTS), science process skills, and others.        Keywords: PODE learning model, digital pop-up book, science concept understanding, critical thinking skills, elementary school students.DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1961-1975